Current understanding on Retinitis Pigmentosa: a literature review - Naning Suleman (Frontiers in Ophthalmology)
Retinitis Pigmentosa (RP) refers to a group of inherited retinal disease, often leading to legal and sometimes complete blindness. It is estimated that over a million people are afflicted with RP all over the world and show tremendous genetic and phenotypic heterogeneity, involving over 90 genes in its causation. The present literature review intends to present a qualitative overview of the genetic mechanisms, clinical features, and diagnostic methods of RP, emphasizing genotype-phenotype correlation. Therapeutic advances in gene therapy, stem cell therapies, optogenetics, retinal prosthetics, and pharmacotherapy are reviewed, and the article notes the crucial role that next-generation sequencing has had in facilitating accurate diagnoses and tailored treatment strategies. While no curative treatments have been proposed, emerging therapeutic strategies are claimed to be effective in blunting disease advancement and maintaining or restoring visual function. Patients who are afflicted with RP often undergo a variety of both physical and mental difficulties, hence requiring several eventual, timely interventions for their social-emotional conflicts. This review aims to present insightful information about the paradigm shift in RP diagnosis and treatment, serving as a complete basis for clinicians and researchers working toward the management of retinal diseases.